Persistent right aortic arch in peruvian hairless dog - a case report - Grandez R., Ricardo (2012)
A Peruvian Hairless puppy dog, two months old, presented a history of regurgitation for a month and progressive loss of body condition since weaning. Clinical examination showed an alert status and poor body condition. The patient received supportive treatment and imagenologic studies were taken: cervical and thoracic radiography, and esophagography, indicating a dilated oesophagus cranial to the heart. Euthanasia was performed at the request of the owner. The animal was subjected to pathological examination, showing the persistence of the fourth right aortic arch and ligament arteriosum that joined the pulmonary artery to the anomalous aorta forming a vascular ring, which resulted in the development of pathological changes, secondary to this alteration in the esophagus and trachea. This case represents the first report of a congenital cardiovascular defect in the Peruvian Hairless Dog.